2015
DOI: 10.4178/epih/e2015042
|View full text |Cite
|
Sign up to set email alerts
|

Trends in health-related behaviors of Korean adults: study based on data from the 2008 - 2014 Community Health Surveys

Abstract: Unhealthy lifestyle behaviors such as smoking, alcohol consumption, and physical inactivity (multiple risks) often lead to serious health consequence and impaired health status. The purpose of this study was to investigate the trend in health-related behavioral factors over time among adults in South Korea (hereafter Korea). The data of 1,595,842 Koreans older than 19 years who participated in the 2008-2014 Korea Community Health Survey were analyzed to assess the trend in the prevalence of behavioral risk fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“… 15 Kang et al's study reported an increased risk of alcohol use and marginally decreased walking rate from the 2008–2014 Korea Community Health Survey. 16 …”
Section: Discussionmentioning
confidence: 99%
“… 15 Kang et al's study reported an increased risk of alcohol use and marginally decreased walking rate from the 2008–2014 Korea Community Health Survey. 16 …”
Section: Discussionmentioning
confidence: 99%
“…Other studies reported that severe preeclampsia was developed in 0.49% of Chinese women [ 61 ], 0.5% in Danish [ 62 ], and 0.4% in British study [ 63 ]. Second, because women living in Seoul, the capital of South Korea, showed generally better health conditions than others in small cities or rural areas [ 64 , 65 ], our restriction of the study population to those living in Seoul possibly resulted in low hypertensive disorders of pregnancy compared to other reports. In our previous studies for South Korea, prevalence of preeclampsia in total and severe preeclampsia (requiring MgSO 4 ) was higher (1.2 and 0.9%) than ours [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In many studies of preventive action, these HRBs have been analyzed as single factors, however they have not primarily been analyzed in interaction with each other. In recent years, considerable evidence for the number of HRBs has been established, that is, how many HRBs a person exerts at the same time or throughout their life [ 3 ]. Less is known about specific combinations of single HRBs, that is, the HRB patterns [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%